Iced [large type] - Francis, Felix (Francis, Felix. Dick Francis novel., 2023)
"Miles Pussett is a former steeplechase jockey. Finding himself in St Moritz during the same weekend as White Turf, when high-class horseracing takes place on the frozen lake, he gets talked into helping out with the horses. It is against his better judgment. Seven years before, Miles left horseracing behind and swore he would never return. When he discovers something suspicious is going on in the races, something that may have a profound impact on his future, Miles begins a search for answers. But someone is adamant to stop--and they'll go to any length to do it"--